Analisis Dampak Kenaikan Harga Kebutuhan Pokok Terhadap Tingkat Pengeluaran Masyarakat di Desa Sitada-Tada - Ayani Denni Pasaribu; Amhar Maulana Harahap; Nur Jannah Nasution (Dirosah Islamiyah, 2026)
This study aims to determine the effect of the increase in the price of basic necessities on the level of community expenditure in Sitada-tada Village, Sihapas Barumun District, Padang Lawas Regency and to measure how much the price increase contributes to changes in community expenditure. The study used a quantitative approach with a population of 333 people in Sitada-tada Village and the sample was determined through probability sampling with a random sampling technique. Data were collected through observation, interviews, and questionnaires, then analyzed using multiple linear regression and classical assumption tests. The results showed that the increase in the price of basic necessities had a significant effect on the level of community expenditure. This is evidenced by the t-value of 6.367 which is greater than the t-table of 1.687 with a significance of 0.000 <0.05. In addition, the contribution of the increase in the price of basic necessities to changes in the level of community expenditure was 52.3%, while the remaining 47.7% was influenced by other factors outside the research variables. These findings indicate that the increase in the price of basic necessities is a dominant factor in determining household expenditure patterns in Sitada-tada Village. Therefore, the higher the price of basic necessities, the higher the community's expenditure to meet their basic needs.